2021
DOI: 10.1186/s40981-020-00405-9
|View full text |Cite
|
Sign up to set email alerts
|

An optimal epidural catheter placement site for post-cesarean section analgesia with double-space technique combined spinal–epidural anesthesia: a retrospective study

Abstract: Background Epidural anesthesia affects lower extremities, which often prevents early mobilization postoperatively. The incidence of numbness and motor weakness in the lower extremities with respect to epidural catheter placement site in cesarean section (CS) is uncertain. We aimed to investigate the effect of catheter placement site on postoperative lower extremities numbness and motor weakness in patients who received combined spinal–epidural anesthesia (CSEA) for CS including analgesic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
0
10
1
Order By: Relevance
“…At present, the clinical analgesic methods after cesarean section are mainly patient-controlled epidural analgesia (PCEA) and PCIA, supplemented by oral or intramuscular injection of analgesics, which have their own analgesic advantages, but each one still has different limitations [ 17 ]. Studies have shown that PCEA has a good analgesic effect [ 12 ], which can not only increase the enthusiasm for breastfeeding, but also accelerate the recovery of gastrointestinal function [ 18 ]; however, there are some related complications such as lower limb weakness, numbness and urinary retention [ 19 ]. Hence, there is currently a clear downward trend in the amount of post-cesarean analgesia clinically used by PCEA.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the clinical analgesic methods after cesarean section are mainly patient-controlled epidural analgesia (PCEA) and PCIA, supplemented by oral or intramuscular injection of analgesics, which have their own analgesic advantages, but each one still has different limitations [ 17 ]. Studies have shown that PCEA has a good analgesic effect [ 12 ], which can not only increase the enthusiasm for breastfeeding, but also accelerate the recovery of gastrointestinal function [ 18 ]; however, there are some related complications such as lower limb weakness, numbness and urinary retention [ 19 ]. Hence, there is currently a clear downward trend in the amount of post-cesarean analgesia clinically used by PCEA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Meechan and co-authors [42] let know that anesthesia effects of ropivacaine in their study were inferior to those with lidocaine-epinephrine. A fresh clinical research in Japan [43] support the idea that the more cephalad the epidural catheter is placed, the more the quality of analgesia is, but did not find any difference between epidural catheter placement inT10-11 and T11-12 in post-cesarean section for pain relief. The same study considered that the LA injected via lumbar dermatomes for CS may not provide sufficient analgesia in the lower thoracic dermatome.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, we observed participants in the low thoracic PCEA group exhibited a Bromage motor scale profile similar to that of participants who received epidural morphine, but more participants in the lumbar PCEA group experienced prolonged lower extremity weakness after spinal anesthesia. Recently, Murata et al reported findings related to a retrospective cohort of 205 parturients who received combined spinal-epidural anesthesia for cesarean delivery; they also discovered that epidural catheter placement at the low thoracic interspace reduced lower extremity weakness [51]. However, high heterogeneity in epidural catheter sites was observed in that study because the epidurals were inserted by performing landmark palpation, which lacks the precision required for definitive localization at the epidural level [17].…”
Section: Discussionmentioning
confidence: 99%